Length‐weight relationship of two mudskippers (Gobiidae: Oxudercinae) Oxuderces dentatus (Eydoux & Souleyet, 1850) and Scartelaos histophorus (Valenciennes, 1837) from Dhamara estuary, Odhisa, India. (4th August 2017) - Mahadevan, G.; Ravi, V.; Murugesan, P.
Summary: Oxuderces dentatus and Scartelaos histophorus species were collected seasonally from the Dhamara estuary (Odhisa, India) using scoop nets, cast nets as well as by hand for a period of 1 year (January 2015–December 2015). Length–weight relationships were estimated. Total lengths (TL) for O. dentatus ranged from 42 to 80 mm, and from 58 to 122 mm for S. histophorus . Similarly, total weights of O. dentatus and S. histophorus ranged from 2.5–10.7 g to 7.7–26.5 g, respectively. The ' b ' values estimated for O. dentatus (2.718) and S. histophorus (2.689) were below 3. The condition factors of O. dentatus and S. histophorus were minimum in summer and maximum post‐monsoon.